Elate – A New Student Learning Model Utilizing EDM for Strengthening Math Education - Lakshmi Prabha, S; Mohamed Shanavas, AR (International Journal of Computer Sciences and Engineering, 2025)
The increase of e-learning resources such as interactive learning environments, learning management systems (LMS), intelligent tutoring systems (ITS), and hypermedia systems as well as the establishment of school databases of student test scores has created large repositories of data. These data can be converted into knowledge for enhancing teaching and learning process. This paper proposes a new learning model ELATE (Enhancing Learning And Teaching) for strengthening Mathematics education in school level and proposes a frame work for using Educational Data Mining for knowledge management. This model utilizes Educational Data Mining (EDM) methods to provide results to the learners regarding their performance and skill level and to the teachers about their wards performance and their capabilities. The teachers can use the EDM results to motivate the slow learners and move the over practiced students to the next level. The ELATE frame work proposed in this paper has five levels processing to provide knowledge management services to stakeholders of educational institutions especially for the teachers and students.